2017
DOI: 10.1002/pssb.201600619
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and control of charge transfer in a tunnel junction

Abstract: Charge transfer in a tunnel junction is studied under dc and ac voltage bias using quantum shot noise. Under dc voltage bias $V$, spectral density of noise measured within a very large bandwidth enables to deduce the current-current correlator in the time domain by Fourier transform. This correlator exhibits regular oscillations proving that electrons try to cross the junction regularly, every $h/eV$. Using harmonic and bi-harmonic ac voltage bias, we then show that quasiparticles excitations can be transferre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…34 The basic idea is to attack the problem by working out the Fourier transformation in Eq. (14) within the stationary phase approximation. Here we only outline the procedure, leaving the technical details to the Appendix B.…”
Section: Tuning Distribution Via Voltage Pulsementioning
confidence: 99%
See 1 more Smart Citation
“…34 The basic idea is to attack the problem by working out the Fourier transformation in Eq. (14) within the stationary phase approximation. Here we only outline the procedure, leaving the technical details to the Appendix B.…”
Section: Tuning Distribution Via Voltage Pulsementioning
confidence: 99%
“…7,12,13 Later, Gabelli et al further show that a similar suppression can be realized by using bi-harmonic voltage pulses. 14 Besides, the existence of the electron-hole excitation can also be helpful in certain situation. Moskalets have demonstrated that, driven by the Lorentzian pulse with a half-integer flux, a zero-energy excitation with half-integer charge can be created in the driven Fermi sea at zero temperature, which cannot exist without the presence of electron-hole excitation.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the fluctuations of an electrical current within one output lead were measured in one experiment, the correlations of currents flowing within both output leads were measured in another. In a sense, these works are the culmination of a number of recent works where the cross-correlation noise was measured to count electrons emitted per period [ 3 , 4 ] to demonstrate a tunable fermionic anti-bunching [ 4 , 5 , 6 , 7 ], and the auto-correlation noise at high [ 8 , 9 ] and low [ 10 , 11 ] frequencies was measured to identify a single-electron emission regime. These experimental advances motivate us to take a closer look at how exactly the quantum properties of wave packets manifest themselves in the measured electrical noise [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, if the fluctuations of an electrical current within one output lead were measured in one experiment, the correlations of currents flowing within both output leads were measured in another. In a sense, these works are the culmination of a number of recent works where the cross-correlation noise was measured to count electrons emitted per period 3,4 , to demonstrate a tunable fermionic anti-bunching [4][5][6][7] , and the auto-correlation noise at high 8,9 and low 10,11 frequencies was measured to identify a single-electron emission regime. These experimental advances stimulate us to take a closer look at how exactly the quantum properties of a wave packet manifest themselves in the measured electrical noise [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%